The role of delta radiomics in gastric cancer - Maria Antonietta Mazzei; Valerio Nardone; Letizia Di Giacomo; Giulio Bagnacci; Francesco Gentili; Paolo Tini; Daniele Marrelli; Luca Volterrani (2018)
We have read with great interest and appreciated the paper by Hou et al . entitled “Radiomic analysis using contrast-enhanced computed tomography (CT): predict treatment response to pulsed low dose rate radiotherapy in gastric carcinoma with abdominal cavity metastasis” (1).